Integration of Character Education in the Independent Curriculum: A Case Study of Elementary Schools in Plered District - Saona Saona; Luthfiah Luthfiah; Nur Alifah; Nabilaa Faizatuz Zuhriyah; Elvira Fitriyanti (MASI Mandiri Edukasi, 2026)
The integration of character education in elementary schools remains inconsistent despite the implementation of the Merdeka Curriculum, particularly in semi-rural areas such as the Plered District. This study aims to analyze the effect of project-based Merdeka Curriculum implementation on the integration of character education among elementary school students. A quantitative research design with a survey approach was employed, involving 100 teachers selected through purposive sampling. Data were collected using structured questionnaires and analyzed using simple linear regression to examine the relationship between curriculum implementation and the integration of character education. The results reveal a positive and significant effect of project-based Merdeka Curriculum implementation on character education integration (β = 0.625; p < 0.05), with R² = 0.422, indicating that 42.2% of the variance in character education integration is explained by curriculum implementation. These findings suggest that effective project-based learning enhances students’ internalization of responsibility, discipline, cooperation, and tolerance. The study highlights the strategic role of the Merdeka Curriculum in strengthening character education at the elementary level and provides empirical evidence from a semi-rural educational context.